First record of Gymnogeophagus lipokarenos Malabarba, Malabarba & Reis, 2015 (Teleostei: Cichliformes) from Argentina - Casciotta, Jorge Rafael (2017)
Gymnogeophagus lipokarenos is registered for the first time from Argentina in the Province of Misiones. The species was originally described as endemic to the Upper Uruguay freshwater ecoregion in Brazil. Our findings extend its distribution into the Lower Uruguay ecoregion throughoutthe province of Misiones.